Berczeli Anzelm Károlyhoz - Magyar Telefonhírmondó (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1934)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek